If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(t + 5) = 0 Reorder the terms: -9(5 + t) = 0 (5 * -9 + t * -9) = 0 (-45 + -9t) = 0 Solving -45 + -9t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + -9t = 0 + 45 Combine like terms: -45 + 45 = 0 0 + -9t = 0 + 45 -9t = 0 + 45 Combine like terms: 0 + 45 = 45 -9t = 45 Divide each side by '-9'. t = -5 Simplifying t = -5
| r+3(r-1)=5(r-3) | | f/4=16 | | 4(2n-3)+5n= | | 1/4t=-400 | | 9r=-7.65 | | 4b-6-8b-4= | | 2x-5(3-2x)=5 | | x(3x-2)+x(2x-7)=(5x+3)(x-6) | | -23b=20.7 | | 9y-4y-2y=5 | | y=-3x^2+3x+18 | | 3t-5t=6 | | 8d=4/5 | | 24/x=12/50 | | 6-5y=1 | | 97=-3+5(5-3x) | | (7-v)(3v-2)=0 | | (98x+61y)/1.84=80 | | 5a+6b=140 | | 2-2t-4x=2 | | 6p+7p=-13 | | 9+3j=22 | | 6y+3x=8 | | 6v=-13 | | 56-5h=34 | | 4(8x^2-5)-[6(4x^2-5)+3]= | | 156=3(6w-9) | | 12+6n=84 | | 4x-2[6-(7-4x)]= | | 3.2y-9-5y+4.8x=5.7x | | Xy+x=-3 | | 5(8y-6)-(7y+5)= |